2021
DOI: 10.2516/ogst/2021044
|View full text |Cite
|
Sign up to set email alerts
|

Polymer viscosifier systems with potential application for enhanced oil recovery: a review

Abstract: Due to the growing demand for oil and the large number of mature oil fields, Enhanced Oil Recovery (EOR) techniques are increasingly used to increase the oil recovery factor. Among the chemical methods, the use of polymers stands out to increase the viscosity of the injection fluid and harmonize the advance of this fluid in the reservoir to provide greater sweep efficiency. Synthetic polymers based on acrylamide are widely used for EOR, with Partially Hydrolyzed Polyacrylamide (PHPA) being used the most. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 126 publications
(231 reference statements)
0
4
0
Order By: Relevance
“…Indeed, they explained that the addition of salt caused a decrease in the associative temperature of related polymer which conducted to an increase in viscosity of the polymer solution due to the formation of hydrophobic micro domains from the thermos‐responsive moieties giving rise to both hydrophobic and intermolecular interactions between polymer chains 49 . In addition, variations in the salinity of aqueous polymer systems led to an increase in the viscosity of thermo‐associate polymer solution at early exposure time as reported by Wang et al 50 …”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, they explained that the addition of salt caused a decrease in the associative temperature of related polymer which conducted to an increase in viscosity of the polymer solution due to the formation of hydrophobic micro domains from the thermos‐responsive moieties giving rise to both hydrophobic and intermolecular interactions between polymer chains 49 . In addition, variations in the salinity of aqueous polymer systems led to an increase in the viscosity of thermo‐associate polymer solution at early exposure time as reported by Wang et al 50 …”
Section: Resultsmentioning
confidence: 73%
“…On the other hand, researchers demonstrated the influence of the addition of salt on the increase in the viscosity of the thermo-viscosifying polymer at temperature below 90 C. Indeed, they explained that the addition of salt caused a decrease in the associative temperature of related polymer which conducted to an increase in viscosity of the polymer solution due to the formation of hydrophobic micro domains from the thermos-responsive moieties giving rise to both hydrophobic and intermolecular interactions between polymer chains. 49 In addition, variations in the salinity of aqueous polymer systems led to an increase in the viscosity of thermo-associate polymer solution at early exposure time as reported by Wang et al 50 Prior to the evaluation of the polymeric solution in the presence of a heavy crude oil sample from a high salinity carbonate well located in southern Mexico, the latter was first characterized with the aim to know its physical properties. Data from viscosity measurement crude oil sample carried out at 25 C showed a zero-shear viscosity of 2.26 Pa s. The API gravity was also determined to have a better point of view on the crude oil sample before the evaluation with the synthesized terpolymer.…”
Section: Resultsmentioning
confidence: 88%
“…Hydrophobically associating polymer [8][9][10], as a new type of water-soluble polymer with a small number of hydrophobic groups introduced into the macromolecular chain of the polymer, has become one of the hot spots in the research of polymer materials in the past 30 years. With the deepening of research and the practice verification, it has successfully applied in the pilot test and large-scale application of EOR in oilfield chemical flooding, and has excellent potential in EOR application [11][12][13]. At present, many studies on the synthesis and salt resistance of hydrophobically associating polymers with different molecular structures have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Zou et al [ 44 ] synthesized a cyclodextrin-based polymer and proposed a mixed flooding of host–guest system and surfactant, which not only reduces the interfacial tension of rock–oil–water but also fully controls the oil–water mobility ratio and improves the oil displacement efficiency of mixed flooding. A large number of studies [ 39 , 45 , 46 ] have shown that the modified polymers have specific application requirements in terms of structure and properties, and they have different effects in improving oil recovery. The study of supramolecular chemical systems in petroleum has played an important role in promoting the supramolecular system in improving oil recovery.…”
Section: Introductionmentioning
confidence: 99%